ANALISIS PENDAPATAN USAHA PENGGILINGAN PADI SAWAH “CAHAYA UMMUL” (STUDI KASUS) DI DESA LAKATAN KECAMATAN GALANG KABUPATEN TOLITOLI - Yanti Sasmita; Merike Apriyanti (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
This study aimed to determine the income generated by "Cahaya Ummul" rice milling entrepreneurship for one year production and to determine its feasibility in Lakatan village, Galang subdistrict, Tolitoli district. This research was carried out in May - June 2017. Samples were purposively selected.  Primary and secondary data were gathered through observations, survey and direct interview.  The data was analyzed using income and feasibility analyses. The research results showed that the income of "Ummul Light" rice milling entrepreneurship in Lakatan Village, Galang subdistrict, Tolitoli district was IDR 234,492,017 for one year production or for two planting season of wetland rice and its R/C value was 1.81 meaning that IDR 1 spent for every IDR 1.81 earned in revenue, thus this is an economically feasible entrepreneurship.